The dual role of heme oxygenase in regulating apoptosis in the nervous system of Drosophila melanogaster - Abaquita, Terence Al L.; Damulewicz, Milena; Tylko, Grzegorz; Pyza, Elżbieta (Frontiers in Physiology, 2023)
Increasing evidence from mammalian studies suggests the Janus-face character of heme oxygenase (HO) in oxidative stress-dependent neurodegeneration. The present study aimed to investigate both the neuroprotective and neurotoxic effects of heme oxygenase (HO) after overexpressing or silencing the gene that encodes this protein in the nervous system of Drosophila melanogaster. Our data showed that HO can be pro-apoptotic or anti-apoptotic under different conditions. In young (7-day-old) flies, the apoptotic gene head involution defective (hid) mRNA and the activity of the initiator caspase Dronc increase in the fly’s head after pan-neuronal ho overexpression and pan-neuronal ho silencing as well. In addition, various expression levels of ho produce cell-specific degeneration. Dopaminergic neurons (DA) are particularly vulnerable to changes in ho expression, whereas eye photoreceptors are sensitive only to ho silencing. During aging, the expression of the hid apoptotic gene decreases in fly heads, along with the unprogressive degeneration of DA neurons, in transgenic strains with an increased or decreased HO level. However, we still observed significantly higher activity of caspase Dronc regardless of ho mRNA levels in neurons from older flies. Our results indicate that neuronal HO regulates apoptosis and this process depends on ho expression level, cell types, and age of flies.